Uma experiência de ensino coletivo de violino no Projeto Vale Música em Belém do Pará - BATISTA, Antonio de Pádua Araújo (Universidade Federal do Pará, 2017)
The methodology of collective teaching of musical instruments has gained a significant place within the context of Music Education in Brazil. In state of Para this practice has since the late 1970s, with the Spiral Project implementation at the State Institute Carlos Gomes. Currently, these initiatives have occurred more often through institutions of the third civil society sector, such as foundations, within their highlight the Foundation of Music Amazon and Vale Foundation, responsible for the implementation of the Project Vale Music, object of this research that purpose investigate how is developed to the collective teaching of violin at PVM / PA. This teaching, developed in various steps, has been creating opportunity for its members to acquisition various abilities, within their highlight the instrumental performance in the newly formed Youth Orchestra Vale Music (YOVM), which made her recital debut in December 2009. The project serves a student composed for children from low income families, which integrate the public schools of Greater Belem. The musical level has achieved by students this project for six years of existence was the main motivating aspect this research. To understand the aspects that have contributed to the achievement of this level of musicianship within the project, seek to identify the socio and cultural agents involved in the process collective teaching the violin - students, teachers, parents and / or guardians -, also identify other aspects as objectives, contents and activities, repertoire, methods, physical space and the time used in the project. This research used the descriptive method, with the support literature research, interviews and document analysis. The expected result is an understanding of what is Project Vale Music, developed in the State of Para, and the model used in the development of collective teaching violin in it.